Models and Mechanisms of Metabolic Regulation: Genes, Stress, and the HPA and HPG Axes - Boersma, G. J.; Salton, S. R.; Spritzer, P. M.; Steele, C. T.; Carbone, D. L. (Hormone and Metabolic Research, 2012)
A variety of models have been developed to better understand the mechanisms underlying individual variation in susceptibility to obesity. This review discusses several of these models and explores their role in understanding individual vulnerability to metabolic disease and the environmental factors around which metabolic perturbations occur. Recently, the focus of models has shifted towards heterogeneous populations, in which individuals characterized by a high vulnerability and individuals that are seemingly resistant can be identified. The use of these heterogeneous studies has lead to the identification of several novel biomarkers predicting obesity. This review therefore focuses on nontraditional factors, which are not directly implicated in metabolic regulation. First, the evidence from rodent knockout models for genetic factors involved in obesity is discussed. Second, the role of a stressful environment, particularly the early life environment is investigated along with a discussion of circadian disruption and metabolic disorders. Finally, the impact of sex-steroids, as exemplified by polycystic ovarian syndrome, is discussed. Overall, the data presented in our review demonstrate that in most cases interplay between genetic and environmental factors best predicts disease development. Our review shows that susceptibility to obesity may be explained by complex interactions between traditional homeostatic mechanisms, such as the hypothalamic peptide, and less studied mechanisms, like steroids and neurotrophic factors.
Keywords: polycystic ovary syndrome; glucocorticoids; obesity; neuropeptides